EXPLORING TIKTOK AFFILIATE AS A DRIVER OF DIGITAL BUSINESS TRANSFORMATION MSMEs: A QUALITATIVE STUDY - Santoso, Ardi Eko (Resilience of Small Medium Business, 2025)
Objective:  While prior studies on TikTok marketing largely focus on influencer popularity, engagement metrics, or short-term promotional outcomes, limited attention has been given to how TikTok Affiliate functions as a mechanism of deeper digital business transformation for MSMEs. This study aims to explore how TikTok Affiliate operates as a content-driven social commerce model that reshapes marketing practices, interaction structures, and value creation processes within the digital economy. Research Design & Methods: A qualitative approach was employed using content analysis and non-participatory observation over three months (January–March 2024). Five TikTok Affiliate creators were purposively selected based on follower scale, content consistency, and active affiliate involvement. Data were analyzed from promotional videos and audience interactions, including comments and engagement patterns.   Findings: The findings reveal that TikTok Affiliate enables MSMEs to move beyond transactional online selling toward a content-mediated transformation of digital marketing, characterized by algorithmic visibility, narrative-based persuasion, and interactive consumer engagement. Rather than relying solely on brand-driven promotion, MSMEs benefit indirectly from creators’ storytelling capabilities and TikTok’s adaptive algorithm, which collectively enhance product discoverability, accelerate purchase decisions, and redistribute marketing functions across the platform ecosystem. Implications & Recommendations: This study demonstrates that TikTok Affiliate effectiveness is not merely determined by creator popularity, but by the alignment between content narratives, algorithmic amplification, and audience sense-making. Practically, MSMEs are encouraged to strategically collaborate with creators whose content logic aligns with platform algorithms and audience expectations, while policymakers and platform managers should recognize affiliate ecosystems as a driver of inclusive digital participation. Contribution & Value Added: This study contributes to digital business transformation literature by conceptualizing TikTok Affiliate as an ecosystem-based transformation mechanism, extending influencer marketing research toward a process-oriented understanding of platform-enabled MSME transformation.